Different BCS Class II Drug-Gelucire Solid Dispersions Prepared by Spray Congealing: Evaluation of Solid State Properties and In Vitro Performances - Serena Bertoni; Beatrice Albertini; Nadia Passerini (MDPI AG, 2020)
Delivery of poorly water soluble active pharmaceutical ingredients (APIs) by semi-crystalline solid dispersions prepared by spray congealing in form of microparticles (MPs) is an emerging method to increase their oral bioavailability. In this study, solid dispersions based on hydrophilic Gelucires® (Gelucire® 50/13 and Gelucire® 48/16 in different ratio) of three BCS class II model compounds (carbamazepine, CBZ, tolbutamide, TBM, and cinnarizine, CIN) having different physicochemical properties (logP, pKa, Tm) were produced by spray congealing process. The obtained MPs were investigated in terms of morphology, particles size, drug content, solid state properties, drug-carrier interactions, solubility, and dissolution performances. The solid-state characterization showed that the properties of the incorporated drug had a profound influence on the structure of the obtained solid dispersion: CBZ recrystallized in a different polymorphic form, TBM crystallinity was significantly reduced as a result of specific interactions with the carrier, while smaller crystals were observed in case of CIN. The in vitro tests suggested that the drug solubility was mainly influenced by carrier composition, while the drug dissolution behavior was affected by the API solid state in the MPs after the spray congealing process. Among the tested APIs, TBM-Gelucire dispersions showed the highest enhancement in drug dissolution as a result of the reduced drug crystallinity.